Problems of work - "Hubbard, L.Ron" (Copenhagen, 2007)
Productivity, efficiency, time management and security in the workplace are some of the subjects are covered in this book. As L. Ron Hubbard describes in this book, life is composed of seven-tenths work, one-tenth familial, one-tenth political and one-tenth relaxation. Here, then, is Scientology applied to that seven-tenths of existence including the answers to Exhaustion and the Secret of Efficiency. Here, too, is the analysis of life itself a game composed of exact rules. Know them and you succeed. The Problems of Work contains technology no one can live without, and that can immediately be applied by anyone in the workaday world.
Keywords: Scientology